Low brain-derived neurotrophic factor and high vascular cell adhesion molecule-1 levels are associated with chronic kidney disease in patients with type 2 diabetes mellitus - Chiang, Yu-Hsin; Li, Yu-Hsuan; Chan, Yin-Ching; Cheng, Yu-Cheng; Wu, Junyi; Lin, Jer-An; Huang, Wei-Chang; Lee, I-Te (Frontiers in Endocrinology, 2024)
Background Patients with type 2 diabetes mellitus (DM) have a high prevalence of chronic kidney disease (CKD). Energy imbalance and inflammation may be involved in the pathogenesis of CKD. We examined the effects of brain-derived neurotrophic factor (BDNF) and vascular cell adhesion molecule-1 (VCAM-1) on CKD in patients with type 2 DM. Methods Patients with type 2 DM were enrolled for this cross-sectional study. Fasting serum was prepared to measure the BDNF and VCAM-1 levels. An estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m2 was used as the criterion for identifying patients with CKD. Results Of the 548 enrolled participants, 156 had CKD. Patients with CKD exhibited significantly lower BDNF (median of 21.4 ng/mL, interquartile range [IQR]: 17.0–27.0 ng/mL vs. median of 25.9 ng/mL, IQR: 21.0–30.4 ng/mL, P <0.001) and higher VCAM-1 (median of 917 ng/mL, IQR: 761–1172 ng/mL vs. median of 669 ng/mL, IQR: 552–857 ng/mL, P <0.001) levels than those without CKD. Serum BDNF levels were inversely correlated with VCAM-1 levels (Spearman’s rank correlation coefficient = -0.210, P <0.001). The patients were divided into four subgroups based on median BDNF and VCAM-1 levels (24.88 ng/mL and 750 ng/mL, respectively). Notably, patients in the high VCAM-1 and low BDNF group had the highest prevalence (50%) of CKD. Multivariate logistic regression revealed a significantly higher odds ratio (OR) of CKD in the high VCAM-1 and low BDNF group (OR = 3.885, 95% CI: 1.766–8.547, P <0.001), followed by that in the high VCAM-1 and high BDNF group (OR = 3.099, 95% CI: 1.373–6.992, P =0.006) compared with that in the low VCAM-1 and high BDNF group. However, the risk of CKD in the low VCAM-1 and low BDNF group was not significantly different from that in the low VCAM-1 and high BDNF group (P =0.266). Conclusion CKD in patients with type 2 DM is associated with low serum BDNF and high VCAM-1 levels. BDNF and VCAM-1 have a synergistic effect on CKD. Thus, BDNF and VCAM-1 can be potential biomarkers for CKD risk stratification in patients with type 2 DM.